Experimental Evaluation of GAGG:Ce Crystalline Scintillator Properties Under X-Ray Radiation - Anastasios Dimitrakopoulos; Christos Michail; Ioannis Valais; George Fountos; Ioannis Kandarakis; Nektarios Kalyvas (Crystals, 2025)
The scope of this study was to evaluate the response of Ce-doped gadolinium aluminum gallium garnet (GAGG:Ce) crystalline scintillator under medical X-ray irradiation for medical imaging applications. A 10 × 10 × 10 mm3 crystal was irradiated at X-ray tube voltages ranging from 50 kVp to 150 kVp. The crystal’s compatibility with several commercially available optical photon detectors was evaluated using the spectral matching factor (SMF) along with the absolute efficiency (AE) and the effective efficiency (EE). In addition, the energy-absorption efficiency (EAE), the quantum-detection efficiency (QDE) as well as the zero-frequency detective quantum detection efficiency DQE(0) were determined. The crystal demonstrated satisfactory AE values as high as 26.3 E.U. (where 1 E.U. = 1 μW∙m−2/(mR∙s−1)) at 150 kVp, similar, or in some cases, even superior to other cerium-doped scintillator materials. It also exhibits adequate DQE(0) performance ranging from 0.99 to 0.95 across all the examined X-ray tube voltages. Moreover, it showed high spectral compatibility with commonly used photoreceptors in modern day such as complementary metal–oxide–semiconductors (CMOS) and charge-coupled-devices (CCD) with SMF values of 0.95 for CCD with broadband anti-reflection coating and 0.99 for hybrid CMOS blue. The aforementioned properties of this scintillator material were indicative of its superior efficiency in the examined medical energy range, compared to other commonly used scintillators.